2009
DOI: 10.3109/08977190903289875
|View full text |Cite
|
Sign up to set email alerts
|

bFGF enhances the IGFs-mediated pluripotent and differentiation potentials in multipotent stem cells

Abstract: It has widely been reported that basic fibroblast growth factor (bFGF) promotes proliferation of human stem cells and contributes to the maintenance of their self-renewal capability through repeated replications. In contrast to embryonic stem cells (ESCs), the effects of growth factors on adult stem cells are poorly understood. In human umbilical cord blood-derived multipotent stem cells (hUCB-MSCs), bFGF is associated with an increased number of proliferating cells. Furthermore, expression levels of ESC marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Our previous studies have proven that all three types of hMSCs exhibited self-renewability and multi-lineage differentiation potential. 3, 14, 34 There were no characteristic differences among these hMSCs. The reason for the differential SOX2 expression might arise from the hMSCs source.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our previous studies have proven that all three types of hMSCs exhibited self-renewability and multi-lineage differentiation potential. 3, 14, 34 There were no characteristic differences among these hMSCs. The reason for the differential SOX2 expression might arise from the hMSCs source.…”
Section: Discussionmentioning
confidence: 84%
“…1 Several core ESC transcription factors are also expressed in human mesenchymal stem cells (hMSCs). 2, 3 Octamer-binding transcription factor 4 (OCT4) is a POU domain-containing transcription factor, known to be essential for the stemness and pluripotency of ESCs. 4 OCT4A has conserved roles in ESCs and in human umbilical cord blood-derived MSCs (hUCB–MSCs).…”
mentioning
confidence: 99%
“…In this study, autocrine IGF-1 levels maintain an elevated baseline activity of ERK1/2 signaling required for enhanced self-renewal (higher OCT4), endodermal (higher CYP51) and mesodermal (higher SM22 α ) potential, but weakened neuronal potential (lower Nestin) [84]. Another growth factor which is basic fibroblast growth factor (bFGF) was shown to be required in maintaining stemness and proliferation in hESCs [31, 85] and in MSCs [80, 86, 87]. Further investigation showed that this bFGF effect was mediated via the IGF system that is upregulated by an autonomous expression of IGF-1R, IGF-1, and IGF-2, as shown in umbilical cord MSCs [86].…”
Section: The Role Of Igfs In Msc Multipotency and Self-renewalmentioning
confidence: 99%
“…Another growth factor which is basic fibroblast growth factor (bFGF) was shown to be required in maintaining stemness and proliferation in hESCs [31, 85] and in MSCs [80, 86, 87]. Further investigation showed that this bFGF effect was mediated via the IGF system that is upregulated by an autonomous expression of IGF-1R, IGF-1, and IGF-2, as shown in umbilical cord MSCs [86]. Although both IGF-1 and IGF-2 are involved in mediating stem cell fate changes, IGF-2 appears to be more prominent than IGF-1 in promoting MSC pluripotency/self-renewal.…”
Section: The Role Of Igfs In Msc Multipotency and Self-renewalmentioning
confidence: 99%
“…Human UCB-MSCs and ARPE-19 cells were cultured as previously described [51518]. For RPE differentiation of human UCB-MSCs and AESCs, cells were cultured on culture dishes with the cell culture medium described above.…”
Section: Methodsmentioning
confidence: 99%